Exploring customer relationship management through technology-enabled experience in virtual environment - HAN, Seungyeon (KDI School, 2021)
Purpose of the study: The purpose of the study is to explore the application of introducing Augmented Reality (AR) technology to interact with customers and to enhance decision making via technology-enabled experience particularly needed in the context of COVID-19. Fill the gap: The current research tries to contribute to the extant literature on customer behavior with AR technology by examining not only perceived utilitarian value and perceived hedonic value but also perceived social value and perceived risk on customer satisfaction as well as by investigating potential AR users’ customer behavior, which has not been studied much yet. Research Question: The study tries to answer the two questions: (1) How do customers’ perceived values and perceived risk of AR functions affect customer satisfaction respectively? (2) How does customer satisfaction affect purchase intention and customer loyalty respectively? Methodology: The research applies factor analysis and regression analysis to test the hypotheses and employs ANOVA and mediation effect analysis to explore additional findings. Major findings: The results of the main regression analyses show that customers react more strongly to benefits of AR technology that are helpful to their functional consumption than to other dimension of benefits. Implications: The findings of the study provides managerial and policy implications to develop and advertise the introduction of AR technology with the emphasis on the practical and utilitarian benefits of the technology. The result of this paper will highlight the importance of customer relationship management by providing advanced services to customers through AR technology.
Thesis(Master) -- KDI School: Master of Public Policy, 2021
Keywords: Customer relations--Management; Mobile commerce